Achievement Strategies in Facing Communication Breakdown Used by the Learners in the Basic Speaking Class of Kampung Inggris Jogja - Novia Uswatun Hasanah; Januarius Mujiyanto (English Education Journal, 2022)
The present study examines learners' strategies in a basic speaking class at Kampung Inggris Jogja to overcome communication breakdowns and effectively convey their ideas and messages to their interlocutors. Furthermore, the study aims to investigate the achievement strategies within the framework of Celce-Murcia et al. (1995) in the classroom interactions among the learners at Kampung Inggris Jogja. A qualitative methodology, specifically discourse analysis of spoken interactions, was utilized to analyze the collected data. Data was gathered through observation of the learners' interactions and recording of their conversations. The investigation revealed that the learners at Kampung Inggris Jogja utilized various achievement strategies in their interactions. However, the foreignizing strategy was not observed among the participants. The strategies most frequently employed by the learners included code-switching, literal translation, non-linguistic means, restructuring, and retrieval. Additionally, the study indicated that learning activities, topics, and environments significantly impacted the learners' communication. Internal factors, such as vocabulary mastery, knowledge of proper grammar, and motivation, played a crucial role in the learners' speaking performance. It is essential to acknowledge the limitations of this study and recognize the need for further research to build upon these findings. Nevertheless, the results of this study contribute to a more comprehensive understanding of the strategies utilized by learners to overcome communication problems and have implications for language teaching and learning in similar contexts. The study highlights the significance of the findings for future research and language education.